2018
DOI: 10.1177/1032373218783333
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of the Italian literature to the international Accounting History literature

Abstract: Italian and Anglo-Saxon accounting scholarships are rather different in their philosophical foundations and conceptual categories. Such difference has implications for Italian scholars aiming at contributing to the international accounting history (AH) literature. This work aims to qualify the contribution of Italian scholars to the AH literature. By means of a review of the AH publication patterns of Italian scholars both in Italian and English language, from 2010 to 2016, the analysis compares Italian and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 90 publications
(135 reference statements)
0
16
0
1
Order By: Relevance
“…Many authors who published in IAR during this period (e.g. Antonelli, Coronella, D’Alessio, Fiume and Maran) 12 also produced several works for international journals, including those that were highly ranked, thereby positioning Italian studies within the international arena (Maran and Leoni, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Many authors who published in IAR during this period (e.g. Antonelli, Coronella, D’Alessio, Fiume and Maran) 12 also produced several works for international journals, including those that were highly ranked, thereby positioning Italian studies within the international arena (Maran and Leoni, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that the multiple origins thesis may be more relevant to the nineteenth century but diffusion became increasingly important in the twentieth century, given the greater level of contact that existed with other countries and their firms and ideas. More broadly, Maran and Leoni (2018) have provided an analysis of Italian contributions to the accounting history literature.…”
Section: Italian Developmentsmentioning
confidence: 99%
“…In particular, in Italian Accounting field, the assessment phase has been lived in a difficult because the Italian tradition is based on monographs in Italian and qualitative methods (Maran & Leoni, 2019). The first were penalized for setting the evaluation, the latter have been disadvantaged by the prevailing reference journals domain North American, always oriented quantitative methods.…”
Section: Introductionmentioning
confidence: 99%
“…During the work, we will follow a qualitative method, examining the Italian legislation and placing it in a conceptual framework, obtained by analyzing the international literature. The analysis that we intend to conduct is more oriented towards a popular article, highlighting the absence of several Italian journals on the international scene with a limitation of the diffusion of national research and a classification with accreditation of national journals in international rankings (Maran & Leoni, 2019).…”
Section: Introductionmentioning
confidence: 99%